Governor Reagan : His Rise to Power - Cannon, Lou (New York Public Affairs, 2003)
Ronald Reagan was a fifty-three-year-old movie actor, past president of the Screen Actors Guild, and former host of the television show General Electric Theater when he gave a dramatic nationally televised speech the year before for Barry Goldwater, the Republican presidential nominee. Goldwater lost in a landslide, but the speech had cast Reagan in the new role of potential candidate
Include Illustration, Note, Bibliography and Index
Keywords: California -- Politics and government -- Governors -- Reagan, Ronald